Assessment of bio-aggregate concretes' properties with rice residue. (15th July 2022) - Amantino, Guilherme Miguel; Hasparyk, Nicole Pagan; Tiecher, Francieli; Toledo Filho, Romildo Dias
Abstract: Agro-industrial activity leads to abundant generation and disposal of waste, which is an attractive source of material for the replacement of fine natural aggregates. These materials are known as bio-aggregates. The study aims to evaluate bio-concretes with bio-aggregates from rice. For this purpose, a SCM of rice husk ash (RHA) was used in partial substitution to cement at 8% (by mass), and the incorporation of rice husk (RH) was performed by replacing natural sand at 5% and 10% levels, by volume. The mechanical and thermal behavior, as well as some physical properties were evaluated in comparison to a reference concrete (without RH), over time and up to 6 months. Based on the results, it was found that the incorporation of RH produced bio-concretes with a good thermal performance due to its lower density, despite the reduction in the mechanical properties and the increase of levels of plastic deformation. This study shows the potential of bio-concretes cast with bio-aggregates from rice waste to be applied for panels or insulating components for buildings. Highlights: Design of a lightweight concrete based on rice residues. Influence of rice husk incorporation as bio-aggregate in the deformability of concrete. Lightweight concrete containing rice husks has better thermal insulation. Bioconcrete containing low rice husk content has satisfactory compressive strength as well as drying shrinkage.